1990
DOI: 10.1093/nar/18.12.3529
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional slippage occurs during elongation at runs of adenine or thymine inEscherichia coli

Abstract: A run of 11 adenine or thymine residues at the 5' end of an out-of-frame lacZ gene causes a high level of beta-galactosidase expression in E. coli. This effect was not observed for a run of guanine residues. Reverse transcription of mRNA isolated from E. coli containing the run of 11 A's reveals heterogeneity of transcript length while reverse transcription of mRNA isolated from S. cerevisiae containing the same gene shows no heterogeneity. Protein sequencing of the beta-galactosidase molecules derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
142
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 33 publications
10
142
0
Order By: Relevance
“…As an alternative to translational rephasing by ribosomes, frameshifted proteins could also arise from TS, which introduces or deletes nucleotides at runs of adenines or thymines in mRNA during transcription by RNA polymerases (Wagner et al, 1990;Volchkov et al, 1995). We generated cDNA from RNA that had been produced in rabbit reticulocyte lysate by T7 RNA polymerase with HCV-1 and Mut1 plasmids.…”
Section: Ts Occurs At the Adenine Cluster In Vitromentioning
confidence: 99%
“…As an alternative to translational rephasing by ribosomes, frameshifted proteins could also arise from TS, which introduces or deletes nucleotides at runs of adenines or thymines in mRNA during transcription by RNA polymerases (Wagner et al, 1990;Volchkov et al, 1995). We generated cDNA from RNA that had been produced in rabbit reticulocyte lysate by T7 RNA polymerase with HCV-1 and Mut1 plasmids.…”
Section: Ts Occurs At the Adenine Cluster In Vitromentioning
confidence: 99%
“…Homopolymeric tracts, particularly stretches of nine or more As or Ts, are prone to enzyme slippage that can alter the tract length compared with the template molecule (1)(2)(3). Long considered ''hotspots'' for mutation, recent studies have begun to clarify the evolutionary and functional implications of these error-prone genomic regions.…”
mentioning
confidence: 99%
“…31 On the RNA level, although the transcription error rate is considered much lower than those during DNA replication, 32 insertion or deletion of a nucleotide can also occur during transcription leading to a frameshift. 33,34,35 The insertion/deletion is believed to involve a slippage between the DNA and RNA strands similar to the Streisinger DNA slippage model, and also tends to occur more frequently on mononucleotide repeats. However, according to the reported examples to date, insertion/deletions during transcription appear to be more prone to occur on A or T repeats rather than G or C repeats, 33,34 a preference that is opposite to that in DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…13, theoretically there were 3 possible mechanisms of the -1 frameshift: 1) insertion of a G within the GGGGGG repeat at DNA level; 2) insertion of a G within the GGGGGG at RNA level; or 3) a shift of the ribosome one nucleotide position toward the 5' direction at the codon GGG (Gly231) or GGA (Gly232) during translation. Although none of the 3 possible mechanisms could be completely ruled out, it appeared that insertion of a nucleotide (likely G) within the GGGGGG repeat at DNA level is more likely than the other 2 mechanisms since insertion at RNA level has only been reported for A/T but not G/C repeats, 33,34 and frameshifts on Gstring are predominately C1 rather than -1 frameshift. 50,52 A homology search of the Mab-1 frameshifted peptide sequence SCDKTHTCPPCPAPELLGGTVSLPLPPKTQGHPHDLPDP in the NCBI Genbank database (Cur_NR_Prot) 53 using BLAST 54 found that it was partially shared by sequences of 3 IgG HC fragments in mAb samples prepared with peripheral blood lymphocytes of patients.…”
Section: Discussionmentioning
confidence: 99%